Perkembangan Kognitif Siswa SMA N 1 Kasihan Melalui Pembelajaran Kooperatif Learning pada Mata Pelajaran PAI - Elyza Riana; Maskurotul Aini; Fidela Sava Zerlina; Muhammad Fauzul Adzim; Arep Kurniawan; Wahyu Kholis Prihantoro (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to determine how the implementation of the cooperative learning model can contribute to students' cognitive development in Islamic Religious Education (PAI) at SMA Negeri 1 Kasihan. The background of this study is based on the low level of active student involvement in the PAI learning process, which is still dominated by conventional lecture methods. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation of PAI teachers and grade 11 students. The results showed that the implementation of cooperative learning encouraged students to be more active in discussions, think critically, and understand religious concepts in depth. This model also improved social skills, responsibility, and collaboration among students. Thus, cooperative learning not only strengthens the cognitive domain but also develops students' affective and psychomotor aspects in a balanced manner. These findings demonstrate that cooperative learning is effectively used in PAI learning as an effort to create an interactive, collaborative, and meaningful learning process.